THE TEACHERS’ AND STUDENTS’ PERCEPTION ON ENGLISH TEXTBOOK “WHEN ENGLISH RINGS THE BELL” - Syifa Dwi Mutiah; Albiansyah (Paedagogia: Jurnal Pendidikan, 2021)
Abstract The purpose of this study is to compare the student's and teacher’s perceptions about their current English textbook they used. This study categorized as a descriptive qualitative study. The population of VIII grade students (45 students) of junior high school was involved in this study and an English teacher of them too. The questionnaire and semi-structured interview were used as the instrument of this research. Besides, the guideline of the interview and questionnaire was from [1]Cunningsworth's (1995) theory which is explained about the book evaluation. The data were analyzed through Google form percentage presentation for the questionnaire while transcription, coding was used for the interview section. The result showed, 75% of students believed that the book they used has good quality. While the rest 25% felt it did not fulfill their expectation and need. Besides, the teachers’ perception supports it with some of the books’ part lacks organization and employed too many vocabularies. Whereas the students felt their current level was not suitable with the teachers’ beliefs, but the teacher believed that it was appropriate with the students’ level. So, there were few different perceptions between them. However, the teacher believed that her role in helping students with textbook usage could help the main point of students’ need due to the teacher has lack of knowledge and awareness to do coursebook evaluation. Therefore, further research needs to be done to make this study more comprehensive.